Community-Level Mental Health and Psychosocial Support During Armed Conflict: A Cohort Study From the Democratic Republic of the Congo, Mali, and Nigeria - Andersen, Ida; Rossi, Rodolfo; Hubloue, Ives (Frontiers in Public Health, 2022)
Introduction: Community-level mental health and psychosocial support (MHPSS) was the first type of MHPSS programme launched by the International Committee of the Red Cross (ICRC) back in 2004. This is the first study to explore whether this type of programme correlates, as intended, with reduced psychological distress and increased daily functioning. Methods: Between December 2018 and June 2020, 6,413 victims of violence received MHPSS through 32 community-level projects in the Democratic Republic of the Congo (DRC), Mali and Nigeria. Symptoms of psychological distress (IES-R or DASS21) and daily functioning (ICRC scale) were assessed before and after the intervention and logistical regression models were used to identify predictors of these symptoms. Findings: Victims of the violence committed by weapon bearers were more likely to show high levels of anxiety prior to MHPSS (aOR 3.51; p<0.0001). Also, victims of physical violence were more likely to show high levels of stress (aOR 1.49; p<0.0001), whereas victims who had witnessed physical violence were more like to report high levels of depression (aOR 2.54; p<0.0001). The most common perpetrators were weapon bearers (76%) and the most common type of violence was rape (46%). Lack of social support stood out as a predictor of both high anxiety (aOR 2.10; p<0.0001) and post-traumatic stress (aOR 2.04; p<0.0001) prior to MHPSS. Following MHPSS, the vast majority of beneficiaries reported a reduction in distress on the DASS21 (96.58%) and the IES-R scales (92.70%) as well as an increase of functioning (82.26%). Adherence to group therapy (x̄7 sessions) was stronger than adherence to individual therapy (x̄4 sessions). A linear trend was found between length of treatment and likelihood of reporting reduced symptoms of depression. Having suffered destruction or loss of property or income predicted less improvement of functioning following MHPSS (aOR 0.90; p=0.044). Conclusion: Receiving community-level MHPSS is associated with increased well-being among the vast majority of beneficiaries. To further enhance the intended health outcomes, it is recommended to increase the length of treatment per beneficiary (≥30 days) and address, where relevant, the financial consequences of violence. Also, a longitudinal study is recommended to assess longer-term changes in MHPSS symptoms.